Towards x-ray waveguide formation upon ion irradiation of a Co thin film on Si(111). (22nd February 2019) - Banu, Nasrin; Roy, S; Satpati, B; Singh, Surendra; Bhukta, Anjan; Chakraborty, P; Basu, S; Dev, B N
Abstract: We have obtained the essential features of x-ray waveguide formation in an ion-irradiated cobalt thin film on Si substrate. Ion irradiation was carried out with 1 MeV Si + ions at a fluence of 5 × 10 16 ions cm −2 . X-ray reflectivity (XRR) experiment shows characteristic dips in the total external reflection region indicating formation of resonant electromagnetic modes—an essential requirement for x-ray waveguides. XRR analysis further reveals formation of a low electron-density layer sandwiched between higher electron-density layers. These are two key requirements for an x-ray waveguide. Computation of x-ray intensity within the irradiated sample shows about 15 times flux enhancement of the electric field within the low electron-density guiding layer.